2021
DOI: 10.1136/bmjqs-2021-013721
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 hospital prevalence as a risk factor for mortality: an observational study of a multistate cohort of 62 hospitals

Abstract: BackgroundThe associated mortality with COVID-19 has improved compared with the early pandemic period. The effect of hospital COVID-19 patient prevalence on COVID-19 mortality has not been well studied.MethodsWe analysed data for adults with confirmed SARS-CoV-2 infection admitted to 62 hospitals within a multistate health system over 12 months. Mortality was evaluated based on patient demographic and clinical risk factors, COVID-19 hospital prevalence and calendar time period of the admission, using a general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 32 publications
1
11
1
Order By: Relevance
“…On the other hand, it contrasted with the results of a study carried out in 85 hospitals in the United States of America in which there was no signi cant association of in-hospital case-fatality rate with overall hospital COVID-19 case volume but rather with more rapid COVID-19 case-growth (32). Other studies indicated, in speci c periods, high COVID-19 hospital prevalence as a risk factor for mortality (33,34). It is important to note that to provide high-quality care, hospitals need resources, investments, teamwork, and expertise.…”
Section: Discussionmentioning
confidence: 55%
“…On the other hand, it contrasted with the results of a study carried out in 85 hospitals in the United States of America in which there was no signi cant association of in-hospital case-fatality rate with overall hospital COVID-19 case volume but rather with more rapid COVID-19 case-growth (32). Other studies indicated, in speci c periods, high COVID-19 hospital prevalence as a risk factor for mortality (33,34). It is important to note that to provide high-quality care, hospitals need resources, investments, teamwork, and expertise.…”
Section: Discussionmentioning
confidence: 55%
“…Moreover, obesity, liver disease and diabetes were independently associated with increased risk of COVID-19 mortality. 17 18 …”
Section: Discussionmentioning
confidence: 99%
“…Studies describe the rapid adjustments hospitals made to staffing, space, and how services were provided to patients [ 27 , 33 35 ], but we know little about how the pandemic affected ongoing quality improvement efforts. Our study helps explain why quality and safety performance appears to have worsened during the pandemic [ 6 , 7 , 36 ]. Participants in our study described going into survival mode and focusing only on the most immediate challenges related to the pandemic.…”
Section: Discussionmentioning
confidence: 99%